Pendekatan Struktur Matriks dalam Sistem Komputasi - Enggi Raynoldman Halawa; Jian R.Sitanggang; Dimas Dwi Kurniawan; Sahatma Sampetua Sinaga; Jonatan Manurung; Selly Annisa Binti Zulkarnain (Journal Educational Research and Development | E-ISSN : 3063-9158, 2026)
Matrix structure is a fundamental concept in linear algebra that plays a crucial role in modern computing systems. Matrices are used as structured data representations in various applications such as digital image processing, artificial intelligence, control systems, and computer graphics. This study aims to comprehensively analyze the concept of matrix structure and its implementation in computing systems. The method used is a literature study with a descriptive-analytical approach to various scientific sources. The results of the study indicate that the matrix approach can improve computational efficiency, simplify complex system modeling, and support parallel computing on modern hardware such as GPUs. Furthermore, matrices also play a role in algorithm optimization and numerical solutions. However, the use of matrices on a large scale has limitations such as high memory requirements and increased computational complexity. Therefore, the development of more efficient optimization methods and computational techniques is needed to maximize the use of matrices in modern computing systems.